Secondary predictors of ovarian hyperstimulation syndrome development - Aiziatulova, E. M. (Zaporozhye Medical Journal, 2019)
In the treatment of infertility by the method of fertilization in vitro, such a serious complication as ovarian hyperstimulation syndrome (OHSS) can occur. Primary predictors of OHSS development are widely used in practice while selecting controlled ovarian stimulation patterns. The identification and evaluation of secondary predictors of OHSS development is relevant. Aim. To identify and evaluate secondary predictors of OHSS in women at high risk of OHSS. Materials and methods. The study included 240 women at high risk of developing ovarian hyperstimulation syndrome, 63 of these women subsequently developed ovarian hyperstimulation syndrome, and 177 did not. To identify secondary predictors, a number of preovulatory follicles and oocytes was evaluated, estradiol levels, vascular endothelial growth factor (VEGF) and interleukin‑6 (IL‑6) were defined in the blood serum and follicular fluid. Results. Compared to women without OHSS, there was a statistically significant increase in the number of preovulatory follicles, oocytes, estradiol, VEGF, IL‑6 in the blood serum and follicular fluid in OHSS patients. There was a direct correlation between the serum and follicular fluid levels of estradiol (rs = 0.85; 95 % CI 0.80–0.89; P < 0.001), VEGF (rs = 0.76; 95 % CI 0.69–0.81; P < 0.001) and IL‑6 (rs = 0.67; 95 % CI 0.58–0.74; P < 0.001). Secondary predictors of OHSS was the number of preovulatory follicles ≥30 for two ovary (sensitivity – 46.0 %, specificity – 91.0 %), the number of oocytes ≥19 (sensitivity – 87.3 %, specificity – 97.7 %), serum estradiol levels ≥4800 pg/ml (sensitivity – 74.6 %, specificity – 96.6 %) and estradiol in follicular fluid – ≥725000 pg/ml (sensitivity – 98.4 %, specificity – 97.7 %), serum VEGF ≥ 30 pg/ml (sensitivity – 76.2 %, specificity – 98.3 %) and VEGF in follicular fluid ≥500 pg/ml (sensitivity – 87.3 %, specificity – 97.2 %), IL‑6 in serum ≥4 pg/ml (sensitivity – 65.1 %, specificity – 98.9 %) and IL‑6 in follicular fluid ≥8.5 pg/ml (sensitivity – 90.5 %, specificity – 98.3 %), respectively. Conclusions. The predictors of OHSS should be taken into account to reduce the risk of its development. In identifying secondary predictors of OHSS development, it is necessary to use preventive measures consisting in discontinuation of luteal phase support, vitrification of all embryos and their transfer in subsequent thawed cycles.